The potential of sustainable agricultural practices to enhance soil carbon sequestration and improve soil quality - Moloto, K. P. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sustainable Development, Planning and Management))--University of Stellenbosch, 2010.